A. M. Gorky - Brodsky, Isaak Izrailevich
Artwork; Portrait of Maxim Gorky with turbulent Russian coast behind him Reproduction of portrait by I. Brodsky of Alexei Maximovich Peshkov. Original title: A. M. Го́рький PO-0902